Causes of formation and characteristics of water-fuel emulsions - Максютинський, П. Ф.; Козаченко, О. І.; Маніта, С. Л. (Proceedings of National Aviation University (archive), 2000)
Considered are the causes of formation and characteristics of water-fuel emulsions in fuel tanks of aircrafts - dispersion and stability (time of water emulsion fallout) Determined is distribution of emulsion water in fuel according to microdrops size caused by mechanical dispersion. It is shown that water-fuel emulsion formed by ultrasonic dispersion is similar to that formed by condensation